2008
DOI: 10.1088/1741-2560/5/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Selective extracellular stimulation of individual neurons in ganglia

Abstract: Selective control of individual neurons could clarify neural functions and aid disease treatments. To target specific neurons, it may be useful to focus on ganglionic neuron clusters, which are found in the peripheral nervous system in vertebrates. Because neuron cell bodies are found primarily near the surface of invertebrate ganglia, and often found near the surface of vertebrate ganglia, we developed a technique for controlling individual neurons extracellularly using the buccal ganglia of the marine mollus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…To extracellularly record from a motor neuron, an extracellular glass electrode was gently pressed onto the sheath above the neuron's soma (Lu et al, 2008;McManus et al, 2012, their Fig. 5).…”
Section: Introductionmentioning
confidence: 99%
“…To extracellularly record from a motor neuron, an extracellular glass electrode was gently pressed onto the sheath above the neuron's soma (Lu et al, 2008;McManus et al, 2012, their Fig. 5).…”
Section: Introductionmentioning
confidence: 99%
“…Note that it is still possible to activate neurons that are not at the surface via extracellular stimulation. However, our model 5 has showed that the stimulation may lose specificity when the target neuron is deeper than the neighboring neurons. When the neuron is deeper, the electrode-to-soma distance will be greater and higher current will be needed to activate this neuron, which may be high enough to activate other surface neurons nearby.…”
Section: Discussionmentioning
confidence: 94%
“…To locate a candidate neuron, use the manipulator to gently press the tip of the extracellular glass electrode down onto the sheath over the center of the neuron soma 5 (Figure 3), which is the best location for stimulation and recording selectivity 5 . Since the threshold current for activating a neuron increases linearly with electrode-to-soma distance 5 , the stimulation selectivity will become worse when the electrode is moved away from the center of the target neuron toward a neighboring neuron. 3.…”
Section: Identifying Motor Neurons Within a Motor Poolmentioning
confidence: 99%
See 2 more Smart Citations